“Never Give Up. The Creator Has Good Things in Store for You”: Risk Factors, Protective Factors, and Evidence of Resilience for Canadian Indigenous Women Abused by Intimate Partners - Ogden, Cindy L. (Violence against women, 2025)
Canadian Indigenous women often experience severe partner violence and child abuse, but few studies holistically examine risk and protective factors and evidence of resilience that affect their well-being. This mixed-methods secondary analysis explored the experiences of 40 Canadian Indigenous abused women. Risk factors included intimate partner violence (IPV), childhood abuse, poverty, colonization, and disability. Protective factors included formal and informal support, community support, spirituality, and childhood residence. Evidence of resilience is from interview quotes and none of the measures of depression, mental distress, and posttraumatic stress disorder was in the clinical range. Despite significant IPV and childhood abuse, the women's resilience is highlighted.